RECEPTION OF THE IDEAS OF PLANETARY UNITY OF PEOPLE IN THE PHILOSOPHY OF COSMISM - Ашиток, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
RECEPTION OF THE IDEAS OF PLANETARY UNITY OF PEOPLE IN THE PHILOSOPHY OF COSMISMIntroduction. Appeal to the spiritual heritage of representatives of cosmism is caused necessity of creating a modern concept of sus-tainable development of human civilization that will bring together healthy people and people with disabilities. Aim and tasks. The aim of the article is to study the ways of forming the planetary unity of people with psycho-physical peculiarities and without them in the con-text of the philosophy of cosmism. The tasks of the article are to consider the views of the cosmists on the global unity of mankind, to study the basic models of disability, to outline a model that can provide the indicated unity, to analyze changes in terminology. Re-search methods: the paper uses general scientific and special research methods. The main among them was the method of compara-tive analysis. In addition, induction, deduction, analysis, etc. were used. Research results. To date, country proclaims the equality of rights and freedoms of man and citizen, including people with disabilities. The presence in the social structure of a significant number of persons with signs of disability determines the importance of the problem. The article considers the definition of disability from the view-point of various theories, describes the medical and social disability models, based on various views on the causes of disability. Discusion. The traditional paradigm of disability is burdensome for the economy. The social paradigm does not take into account the spec-trum of psychophysical capabilities of persons with disabilities, the need for maximum state assistance for some of them. There is a need in creating for a new paradigm that rejects the notion of disability. Conclusion. The new model of disability must protect the rights of persons with disabilities and become the basis for the unity of all people on Earth, regardless of their mental and physical characteristics.